Successful treatment of syringotropic CD8+ mycosis fungoides accompanied by hypohidrosis with vorinostat and retinoids. (11th September 2012) - Kakizaki, Aya; Fujimura, Taku; Mizuashi, Masato; Watabe, Akiko; Kambayashi, Yumi; Aiba, Setsuya
Abstract: We describe a 34‐year‐old Japanese man with syringotropic CD8+ mycosis fungoides (MF) accompanied by hypohidrosis who was treated with vorinostat and retinoids. Interestingly, immunohistochemical staining for dermcidin revealed a decrease of sweat in the eccrine glands, and a sweat test by the iodine starch method proved hypohidrosis in the MF‐affected areas. Six months after treatment with this combination therapy, the patient's advanced MF was under control.